Antimicrobial Doses in Continuous Renal Replacement Therapy: A Comparison of Dosing Strategies - Anna P. Kempke; Abbie S. Leino; Farzad Daneshvar; John Andrew Lee; Bruce A. Mueller (Critical Care Research and Practice)
Purpose. Drug dose recommendations are not well defined in patients undergoing continuous renal replacement therapy (CRRT) due to limited published data. Several guidelines and pharmacokinetic equations have been proposed as tools for CRRT drug dosing. Dose recommendations derived from these methods have yet to be compared or prospectively evaluated. Methods. A literature search of PubMed, Micromedex, and Embase was conducted for 40 drugs commonly used in the ICU to gather pharmacokinetic data acquired from patients with acute and chronic kidney disease as well as healthy volunteers. These data and that obtained from drug package inserts were gathered for use in three published CRRT drug dosing equations. Doses calculated for a model patient using each method were compared to doses suggested in a commonly used dosing text. Results. Full pharmacokinetic data was available for 18, 31, and 40 agents using acute kidney injury, end stage renal disease, and normal patient data, respectively. On average, calculated doses differed by 30% or more from the doses recommended by the renal dosing text for >50% of the medications. Conclusion. Wide variability in dose recommendations for patients undergoing CRRT exists when these equations are used. Alternate, validated dosing methods need to be developed for this at-risk patient population.